Determination and Comparison of Aspartame Level in Low Calorie Table Top Sweeteners by Ultraviolet Visible Spectroscopy - Narjis Naz ,; Subreena Altaf, (Journal of Basic & Applied Sciences, 2018)
The analysis of aspartame was done in table top sweeteners using Ultraviolet visible Spectroscopy. The method is based on the formation of manganate ion (MnO42-) when potassium permanganate oxidizes aspartame. The analysis was carried out at a fixed wavelength of 600nm exactly after 48 minutes of sample preparation using 1mL of 0.01M KMnO4 and 2mL of 1.0M NaOH. A linear calibration graph was obtained with the regression coefficient of 0.9999 and the percentage recovery was in the range of 92.7-101.6%. The Relative standard deviation for the method was found to be 1.03%.